Optimization of Ion Implantation processes for 4H-SiC DIMOSFET. Issue 55 (18th May 2016) - Piluso, N.; Fontana, E.; Di Stefano, M.A.; Litrico, G.; Privitera, S.; Russo, A.; Lorenti, S.; Coffa, S.; La Via, F.
Abstract: In this paper the defects generated by ion implantation in 4H-SiC DIMOSFET (Double Implanted MOSFETs), and their evolution after annealing process, have been studied in detail. The point defects generated by the source or body implantation process have been detected by micro-photoluminescence (µPL) and the effect of these defects on the electrical characteristics of the DIMOSFET has been studied. The role of the annealing process has been carefully investigated by using different temperatures. It appears fundamental for the restoring of the crystal damage. The effect of the ion implantation dose has been investigated as well. By reducing the source ion implanted dose a large decrease of point defects has been detected and a considerable improvement of the electrical characteristic of the DIMOSFET has been observed.